The asymmetric effect of COVID-19 government interventions on global stock markets: New evidence from QARDL and threshold regression approaches. Issue 4 (2nd October 2022) - Abdullah, Mohammad; Wali Ullah, G. M.; Chowdhury, Mohammad Ashraful Ferdous
ABSTRACT: We examine the asymmetric effect of COVID-19 government interventions on global stock markets using a sample of 61 countries over the period of January 2020 to December 2021, applying Quantile ARDL (QARDL) and panel threshold regressions. The QARDL results show a heterogenous effect of government interventions on stock markets which varies along with country income level and stock market size. Additionally, the panel threshold regression reveals a positive effect before and a negative effect after the threshold level of government interventions. Our findings can assist policymakers to formulate intervention plans in limiting financial turbulence.